Uncertainty spill-overs: When policy and financial realms overlap - Emanuele Bacchiocchi; Catalin Dragomirescu-Gaina (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2022)
No matter its source, financial- or policy-related, uncertainty can feed onto itself, concealing its true origin and leading to identification challenges in empirical applications. We add to the existing stock of analytical methods able to disentangle among various types of uncertainty shocks, by generalising an identification approach based on magnitude restrictions to a multi-country setting. Within the Euro Area, we find evidence of sizable spill-overs arising from country-specific uncertainty shocks, with financial realm being a more important source than the policy realm. By leveraging on the flexibility of our identification strategy, we quantify the valuation 'mistakes' that arise from the inability to separate uncertainty shock types within a given country; we then show that the implicit under/over-valuations can be related to some simple cross-sectional indicators of financial and political stability, especially before the 2008/2009 crisis. A comparison between the responses of sovereign yields within and outside the Euro Area suggests strong within institutional arrangements and risk-sharing mechanisms that can blur the thin separation line between uncertainty shock types. In this context, we find that ECB reacted to those identified uncertainty shocks with the highest potential to spill over abroad, thus filling a leadership vacuum within the Euro Area.
Keywords: C3; E58; E60; F36; F40; 330; policy uncertainty; financial integration; global VAR; unconventional monetary policy